The development of facility standards for common outpatient procedures and implications for the context of abortion - Nancy F. Berglas; Sarah C. M. Roberts (BMC, 2018)
Abstract Background In recent years, an increasing number of states have enacted laws that impose specific requirements for facilities in which abortions are performed. In this study, we sought to understand the processes used to develop facility standards in the context of other, less politically charged areas of health care and consider implications for the context of abortion. Methods We conducted key informant interviews with 20 clinicians and accreditation professionals involved in facility standards development for common outpatient procedures (endoscopy, gynecology, oral surgery, plastic surgery). We examined the motivations for and processes used in facility standards development, use of scientific evidence in standards development, and decision-making in the absence of evidence. Interview data were thematically coded and analyzed using an iterative approach. Results In contrast to U.S. state laws that target abortion facilities, standards for other outpatient procedures are commonly set by committees of clinicians organized by professional associations or accreditation organizations. These committees seek to establish standards that ensure patient safety without placing unnecessary burden on clinicians in practice. They aim to create evidence-based standards but can be hampered by lack of relevant research. In the absence of research evidence, committees rely on their clinical expertise and sense of best practices in decision-making. According to respondents, considerations of potential harm (e.g., deeper levels of sedation, invasiveness), rather than the specific procedure, should prompt additional requirements. Conclusions If facility standards in the context of abortion were developed through processes similar to other outpatient procedures, 1) professionals who perform the procedure would be involved in standards development and 2) in the absence of clear research evidence, the expertise of clinicians, and the guidelines and standards of other organizations, are used to describe a best practice standard of care.